RENT EXTRACTION PADA PERUSAHAAN DENGAN STRUKTUR KEPEMILIKAN TERKONSENTRASI DI BURSA EFEK INDONESIA - Ni Ketut Surasni; Hermanto Hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This study aims to examine the existence of rent extraction by examining the market reaction to the increase and decrease in dividends. For this purpose, the method used is an event study. Market reaction is measured using cumulative average abnormal return (CAAR). If CAAR is high> CAAR is low. hence rent extraction is proven, dividends are proven to relieve conflict between majority and minority. By using the difference test, it was not proven that high CAAR> low CAAR. These results indicate that investors do not react to increases or decreases in dividends. In companies with a concentrated ownership structure, dividends do not function as a reliever for conflicts between majority and minority. Kata kunci: Concentrated ownership structure, rent extraction, dividends.